2015
DOI: 10.1042/bst20150078
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of gene and tissue networks regulating insulin signalling in flies and vertebrates

Abstract: Fruit flies have emerged as a powerful tool to investigate metabolism. Not only are gene structures and gene networks that control metabolism conserved through evolution, but the interactions among organs to store and process metabolites have strong similarities between flies and humans. Accordingly, the Drosophila system has the potential to address human disorders associated with metabolic dysfunction including obesity, type 2 diabetes and lipotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…The key molecular components of the 20HE, IS, and TOR signaling pathways are well conserved throughout evolution (43,46,47), and a summary of these pathways presented in Fig. 3A documents that our custom array is well-represented with putative C. costata gene probes of the 20HE, IS, and TOR pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key molecular components of the 20HE, IS, and TOR signaling pathways are well conserved throughout evolution (43,46,47), and a summary of these pathways presented in Fig. 3A documents that our custom array is well-represented with putative C. costata gene probes of the 20HE, IS, and TOR pathways.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the silencing of the insulin (IS) and target of rapamycin (TOR) signaling pathways has often been implicated as an important regulator of insect diapause (37)(38)(39)(40)(41). Active IS and TOR pathways promote cell proliferation and organismal growth (42,43), whereas the silencing of these pathways is linked to the suppression of growth/ development and enhanced stress response, phenotypic changes that are also characteristic of insect diapause (44-46) (for more details, see Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…Rapid responses to metabolic changes are challenges faced by all organisms, and the potential importance of insulin signalling in such responses is highlighted by the high conservation of insulin structure and insulin signalling pathways across vertebrates and invertebrates, with evolutionary lineages that diverged long ago [39,40]. However, the last common ancestor between teleost fishes and humans is estimated to have lived approximately 450 million years ago [41], and while insulin and other hormones are structurally conserved across the vertebrates, whether secretory regulation and functional consequences are as conserved is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…This receptor (DInR or InR) was shown to function similarly to the mammalian insulin receptor in that it has tyrosine kinase activity and autophosphorylates in response to human insulin, but not other peptide hormones (Fernandez-Almonacid & Rosen, 1987). These studies and many others demonstrated that insulin and insulin-like signaling (IIS) pathways are shared between flies and humans (reviewed in Das & Dobens, 2015; Kannan & Fridell, 2013; Oldham, 2011; Taguchi & White, 2008; Teleman, 2010). Interestingly, insects express a large number of Ilps, from eight in Drosophila to many more in other invertebrates, but only one insulin-like receptor (reviewed in Wu & Brown, 2006).…”
Section: Drosophila Models Of Type 1 Diabetesmentioning
confidence: 98%
“…These include gestational diabetes, maturity onset diabetes of the young (MODY) and Metabolic syndrome (MetS) (also known as Syndrome X). Because of their wide prevalence, diabetes and related disorders have been studied and reviewed extensively, as have the roles of insulin signaling pathways in both mammals and Drosophila (for examples, Baker & Thummel, 2007; Das & Dobens, 2015; Garofalo, 2002; Goberdhan & Wilson, 2003; Kahn et al, 2005; Lasko, 2002; Owusu-Ansah & Perrimon, 2014; Padmanabha & Baker, 2014; Tatar, 2004; Wu & Brown, 2006 #141). In this chapter, we have focused on recent studies in which Drosophila models have been developed for specific disease features and types.…”
Section: Introductionmentioning
confidence: 99%